Analisis Faktor Yang Berhubungan Dengan Kejadian Low Back Pain Di PT. Maruki International Indonesia Makassar - Adelia Suryani Jonathan; Mulyadi Mulyadi (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2020)
Ergonomic is compatibility between working tools and workers who not suitable can cause workers to feel uncomfortable and decreased worker of productivity. One from things related of ergonomics is work position. In this case such as long standing, lifting, pushing, sitting position, etc. Workers of body activity that is not good in the long term will cause Low back pain (LBP) or Lower Back Pain (NPB).The aim of this study was to analyze the factors associated with the incidence of Low Back Pain in PT. Maruki International Indonesia Makassar .. This research is an observational analytic study with a cross sectional study design, a total sample of 58 people and using a purposive sampling method and data analysis is tested by conducting a statistical test that is chi square.The results showed there was no relation between age and the incidence of low back pain with P-value is 0.697> 0.05, there was a relation between duration time of work and the incidence of low back pain with P-value is 0.004 <0.05 and there was a relation between work ergonomics with the incidence of low back pain with P-value is 0.012 <0.05.Based on the results of this study concluded there ere no relation between the variables with the incidence of low back pain in workers at PT. Maruki International Indonesia Makssar in the factory section 1. Suggestions It is expected that workers improve their working methods of paying attention to health by applying ergonomic work principles to avoid injury, and other occupational diseases.Keywords: Low Back Pain, Age, Duration Of Work, Ergonomics